2019
DOI: 10.1371/journal.pone.0217077
|View full text |Cite
|
Sign up to set email alerts
|

Role of the light fraction of soil organic matter in trace elements binding

Abstract: The light fraction of soil organic matter (LF) has a rapid turnover and may be potentially metal-enriched, but the interaction between this pool of organic matter and trace elements has not been well studied. The present study aimed to investigate changes in LF content and its effect on heavy metals distribution and extractability in long-term contaminated soil by smelting activity. An incubation experiment was conducted on a surface horizon of Brunic Arenosol sampled from the previously-existing sanitary zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…In the same study, it was also shown that this size fractionation corresponded to the age of the aggregates with increasing C14 levels recorded for the smaller fractions (Quenea et al, 2008). Recent work from Wiatrowska and Komisarek (2019) has shown that binding on metals to the light fraction of fresh organic matter added to soil via manure or straw does not differ substantially from that of the original soil carbon pool, which would facilitate a single model concept to describe binding on metals to soil carbon in soil. On the other-hand, Li et al…”
Section: Outlook On Scenario-analysesmentioning
confidence: 76%
“…In the same study, it was also shown that this size fractionation corresponded to the age of the aggregates with increasing C14 levels recorded for the smaller fractions (Quenea et al, 2008). Recent work from Wiatrowska and Komisarek (2019) has shown that binding on metals to the light fraction of fresh organic matter added to soil via manure or straw does not differ substantially from that of the original soil carbon pool, which would facilitate a single model concept to describe binding on metals to soil carbon in soil. On the other-hand, Li et al…”
Section: Outlook On Scenario-analysesmentioning
confidence: 76%
“…Linear models show a statistically significant strong (R 2 adj .=0.72) effect of OMP on the content of mobile forms of Mn (1), as well as a statistically significant but weak (R 2 adj .=0. 19) effect of pH on the content of mobile forms of Сu (2).…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al [18] note a decrease in Cu sorption by soil during the formation of complexes with soluble organic matter. There is also an opinion that labile fractions of OM may play a key role in the control of Cu mobility, which may promote Cu migration in acidic soils [19].…”
Section: Discussionmentioning
confidence: 99%
“…is suggested that it was more present in fine fractions (size <1 mm), as shown in Table 6 and proposed by many authors [46], and/or that it was more strongly retained in the coarse fraction (size >1 mm). Pb ions would not be readily available to the ligand as explained when discussing m/V effect: the chelator, EDTA or NTA, had to compete with the bonding strength of Pb to the soil and probably to the other constituents of the soil, in particular, organic matter [48]. As we have seen in Table 6, Pb was more present in the fine fraction than in the large fraction of the soil, and therefore it was more extracted from fraction F than from fraction C. is could explain the effect of the size of the soil particles on the extraction of Pb.…”
Section: Effect Of Soil's Particle Sizementioning
confidence: 99%